Stoichiometry and stable isotopes of plants and their response to environmental factors in boreal peatland, Northeast China - Wang, Shujie; Wang, Xianwei; Sun, Xiaoxin; Ma, Guobao; Du, Yu; Jiang, Jingyi (Frontiers in Ecology and Evolution, 2022)
The alterations of plant composition and diversity pose a threat to the stability of the carbon pool in boreal peatland under climate change. We collected the samples of three plant functional types (deciduous shrubs, evergreen shrubs, and sedge) in seven permafrost peatlands of the Great Hing’an Mountains, China, and measured the properties of total carbon (TC), nitrogen (TN), and phosphorus (TP), their stoichiometric ratios (C: N, C: P, and N: P), and the stable isotope values (δ13C and δ15N) of six tissues (ranging from leaves to roots). For TC, TN, and TP, the contents had an average of 470.69 ± 1.56, 8.03 ± 0.23, and 1.71 ± 0.61 mg·g−1, respectively. TC contents of sedge were lower than those of shrubs for the whole plant. The allocations of N and P to shrub leaves were higher than to stems and roots. There was a similar trend of TN and TP contents, and stoichiometric ratios from leaves to roots between deciduous shrubs and evergreen shrubs. Shrubs and sedge have similar C: N in leaves and fine roots, while leaves of sedge C: P and N: P ratios were higher than shrubs, mainly showed that sedge is N and P co-limitation and shrubs are N limitation. The values of δ13C and δ15N were significantly higher in leaves and roots of sedge than those of shrubs, which means shrubs have higher nutrient acquisition strategies. These results support the shrubs are expanding in the boreal peatland under climate warming through nutrient competition. TC contents of all deciduous shrubs and sedge tissues were positively linear correlated to MAT and the values of δ13C and δ15N in sedge had significant relationships with MAT and MAP. Our results imply warming can increase plant photosynthesis in boreal peatland, and sedge was more sensitive to climate change. These findings would be helpful to understanding the responses of different plant tissues to climate changes in permafrost peatland.